Factors Inhibiting and Supporting the Critical Thinking Learning Model in the Aqidah Akhlak Subject - Diki Darmawan; Suwendi; Siti Khadijah (Journal of Practice Learning and Educational Development, 2025)
The behavioral shift of Generation Z in the digital era demands a more adaptive and holistic moral education approach in Islamic boarding schools. Consequently, the role of Islamic Education teachers (PAI teachers) must extend beyond instructional duties toward becoming authentic moral exemplars. This study aims to critically analyze students’ perceptions of PAI teachers as moral guides at Pondok Modern Darul Falach Candiroto Temanggung and to evaluate the effectiveness of the moral development strategies implemented. This research employs a qualitative descriptive method, using in-depth interviews, participant observation, and documentation, selected through purposive sampling. Data were analyzed using Miles and Huberman’s model consisting of data reduction, data display, and conclusion drawing. The findings reveal that teacher exemplarity particularly in worship discipline, polite communication, behavioral modesty, and consistency forms the strongest basis for students’ positive perceptions. However, some students noted emotional inconsistency among certain teachers, which may weaken their moral authority. Regarding pedagogical strategies, personal mentoring, spiritual dialogue, and habituation through daily routines were perceived as the most effective, while digital-ethics guidance remains underdeveloped. The study concludes that effective moral development requires the integration of teacher exemplarity, empathetic interpersonal relationships, and innovative approaches aligned with the moral challenges faced by Generation Z.